Kompetensi Digital dan Pelatihan : Kunci Peningkatan Kinerja Pegawai Kementerian Agama Kabupaten Kuningan - Ratu Nursyifa Fathiyatuzzah; Fetty Poerwita Sary (IPM2KPE, 2024)
This research aims to determine the effect of digital competence and training on employee performance. The population in this study were all employees of the Kuningan Regency Ministry of Religion Office with a sample size of 191 employees. The data used in this research comes from primary and secondary data based on the results of questionnaires, interviews and documentation. The sampling method in this research uses probability sampling (random sampling) using the Slovin formula. The analysis technique used is descriptive analysis, classical assumption test, multiple linear regression and coefficient of determination. The research results show that digital competency, training and employee performance are in the good category. Meanwhile, the results of the simultaneous test show that digital competency and training have a significant positive effect on the performance of employees at the Kuningan Regency Ministry of Religion Office by 65%. Keywords: Employee Performance, Digital Competence, Training